Experimental studies on the efficacy of artesunate and oxytetracycline combination against induced BTT in crossbred calves - PATEL, DINESH; MISRAULIA, K S; REDDY, A GOPALA; GARG, U K; SHARMA, R K; GUPTA, BRAJESH KUMAR (The Indian Journal of Animal Sciences, 2014)
The efficacy of artesunate in combination with oxytetracycline was assessed in order to evolve an alternative to standard chemotherapeutic agents against bovine/tropical theileriosis (BIT). Experimental induction of BIT in 12 crossbred male calves with ground up tick supernates prepared from Hyalomma anatolicum anatolicum infected with Theileria annulata resulted in significant (P< 0.01) decrease in TEC, TLC, Hb, PCV, MCHC, total protein and total serum albumin, and significant (P<0.01) increase in body temperature, pulse rate, respiration rate, MCV, total serum bilirubin, alkaline phosphatase and globulin. The calves were divided into 2 groups, A and B, each having 6 calves. All the calves in group B (infected control and provided only supportive therapy) died manifesting typical symptoms and lesions of theileriosis. In group A (treated with artesunate + oxytetracycline + supportive therapy), 2 calves died and the remaining (including the one with cerebral theileriosis) were clinically cured. Thus the efficacy ofartesunate in combination with oxytetracycline was 66.67% and it is suggested that this cqmbination can be used in the treatment of BIT.